EFEKTIVITAS MEDIA PEMBELAJARAN ADOBE ANIMATE BERBASIS ANDROID TERHADAP EFIKASI DIRI SISWA PADA MATERI LAJU REAKSI - Muthiyah Shahirah (KATALIS: Jurnal Penelitian Kimia dan Pendidikan Kimia, 2024)
This research aimed at finding out the effectiveness of using Android based Adobe Animate learning media on Reaction Rate lesson toward student self-efficacy at State Senior High School 3 Pekanbaru. It was pre experiment research with One Group Pretest-Posttest Design. All the eleventh-grade students of MIPA at State Senior High School 3 Pekanbaru in the Academic Year of 2022/2023 were the population of this research. There was one group of samples—the eleventh-grade students of MIPA 2 as the research sample group. The data collection techniques used were questionnaires and interviews. The data were analyzed by using t-test and N-gain test. Based on the calculation result, the score of tobserved (6.670) was higher than ttable (2.032), and the significance score 0.00 was lower than α (0.05). Therefore, H0 was rejected and Ha was accepted. Based on N-gain test, the research sample group was on low category with the respective score 0.23. It could be concluded that the use of Android based Adobe Animate learning media was not effective toward student self-efficacy on Reaction Rate lesson. The updates to Android based Adobe Animate learning media such as application buttons, completeness of material, and sample questions were needed to get better student self-efficacy.